30 The prognostic implication of troponin level in over 3000 patients presenting with atrial fibrillation (NIHR Health Informatics Collaborative AF-trop Study). (May 2019) - Kaura, Amit; Arnold, Ahran; Panoulas, Vasileios; Glampson, Ben; Davies, Jim; Mulla, Abdulrahim; Woods, Kerrie; Omigie, Joe; Shah, Anoop D; Channon, Keith; Weber, Jonathan N; Thursz, Mark R; et al.
Abstract : Background: Patients presenting with atrial fibrillation (AF) often undergo measurement of troponin level, but interpretation of the result is impeded by uncertainty around its clinical importance. Although coronary artery disease (CAD) has been implicated in the prognostic significance of troponin levels in AF, the role of investigating for CAD and its effect on mortality remain unclear. We investigated the relationship between troponin level, coronary angiography and all-cause mortality in real-world patients presenting with AF. Methods: We utilised National Institute for Health Research Health Informatics Collaborative data to identify patients admitted between 2010 and 2017 at 5 tertiary centres with a primary diagnosis of AF who underwent at least one troponin measurement. Patients meeting the eligibility criteria were followed up using routinely collected data, until death or censoring in April 2017. The peak troponin result during the index admission was scaled across assays as multiples of the upper limit of normal (xULN). To model non-linear relationships, we used restricted cubic splines for regression analyses. Results: 3, 121 patients were included in the analysis. Over a median follow-up of 48.1 (IQR 30.5–64.9) months, there were 586 (18.8%) deaths. While troponin levels below 1.3 xULN showed no significant relationship with hazard ratio, at higher troponin levels, a significant positive relationship was demonstrated (figure 1A). 216 (6.9%) patients underwent coronary angiography, with 78 (36.1%) of these patients subsequently undergoing coronary revascularisation. Above the ULN, there was a positive relationship between troponin level and odds of angiography (figure 1B). While there was no significant relationship between troponin level and mortality in patients who underwent angiography (figure 1C), a significant relationship was observed in patients who did not undergo angiography with troponin levels above the ULN (figure 1D). On cox regression analysis, following adjustment for demographic and clinical factors, including troponin level, angiography was associated with a 39% reduction in mortality during follow-up (hazard ratio 0.61, 95% CI 0.42–0.89, p=0.01). Conclusion: Above the ULN, higher troponin levels were associated with higher mortality. Within the normal range, this was not the case. While angiography was not common in patients presenting with AF, the likelihood of angiography increased at higher troponin levels. In cases where angiography was not performed, there was a direct relationship between troponin levels above the ULN and mortality; this was not evident where angiography was performed. Following adjustment for troponin level, angiography was associated with a significant reduction in mortality. The risk of mortality in patients presenting with AF may be mediated by CAD. Clinical trials are warranted to clarify the investigation and treatment of CAD in patients presenting with AF with elevated troponin levels. Conflict of Interest: No conflicts of interest